Implementation of Electronic Signatures and E-Notarization within the Indonesian Notarial Legal Framework - Markus Gunawan; Erniyanti Erniyanti (International Journal of Sociology and Law, 2025)
This research examines the implementation of electronic signatures and e-notarization within Indonesia's notarial legal framework, analyzing the tensions between technological innovation and traditional notarial principles. Indonesia has established basic legal recognition for electronic signatures through Law No. 11/2008 on Electronic Information and Transactions (as amended by Law No. 19/2016) and conceptually acknowledged cyber notary in the explanation of Article 15(3) of Law No. 2/2014 on Notary Positions which mentions "the authority to certify transactions conducted electronically". However, significant regulatory and practical challenges persist due to contradictions between digital concepts and traditional notarial requirements such as physical presence during the notarial process. The research reveals Indonesia lags behind many jurisdictions with similar civil law traditions in e-notarization implementation where the integration of digital elements into notarial systems has enhanced efficiency while maintaining security standards. This study proposes a balanced implementation approach that preserves essential notarial functions of authentication and legal certainty while leveraging technology to enhance accessibility and efficiency, requiring legislative reforms, technical standardization, institutional development, and professional training to create a comprehensive e-notarization framework suited to Indonesia's legal context.